Preparation method of barium titanate-based high-entropy oxide nano material

By combining microchannel reactors and hydrothermal reactions, small-sized, highly crystalline barium titanate-based high-entropy oxide nanomaterials were prepared, solving the problems of grain growth and uneven element distribution in traditional methods, and realizing the improvement of material performance and applicability to industrial production.

CN121005565APending Publication Date: 2025-11-25SHANGHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511284882.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing technologies struggle to produce small-sized, highly crystalline, and uniformly composed barium titanate-based high-entropy oxide nanomaterials. Traditional methods suffer from high-temperature reactions that lead to grain growth and uneven element distribution, and are difficult to meet the demands of large-scale production.

Method used

A barium titanate-based high-entropy precursor was prepared by co-precipitation using a microchannel reactor combined with hydrothermal reaction. The efficient mixing and mass transfer properties of the microchannel reactor were utilized to control the reaction conditions, and the hydrothermal reaction was combined to promote crystallization, resulting in small-sized, highly crystalline barium titanate-based high-entropy oxide nanomaterials.

Benefits of technology

This study achieved efficient preparation of small-sized, highly crystalline barium titanate-based high-entropy oxide nanomaterials under mild conditions, making them suitable for large-scale industrial production. It improved the dielectric properties and temperature stability of the materials, overcoming the shortcomings of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121005565A_ABST
    Figure CN121005565A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of inorganic nano materials, and particularly relates to a preparation method of a barium titanate-based high-entropy oxide nano material. The preparation method comprises the following steps: respectively pumping an aqueous solution of a metal salt and an aqueous solution of a precipitator into a mixer of a microchannel reactor, carrying out a mixed reaction, and aging to obtain a barium titanate-based high-entropy precursor; the metal salt comprises divalent metal salt and tetravalent metal salt; the divalent metal salt comprises barium salt, or barium salt and auxiliary divalent metal salt; the tetravalent metal salt comprises a titanium salt, or the titanium salt and an auxiliary tetravalent metal salt; and mixing the barium titanate-based high-entropy precursor, a barium source and water, and carrying out hydrothermal reaction to obtain the barium titanate-based high-entropy oxide nano material. The barium titanate-based high-entropy oxide nanoparticles with small size and high crystallinity can be efficiently and stably prepared, the defects of a traditional process are overcome, and the method is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic nanomaterials technology, specifically relating to a method for preparing barium titanate-based high-entropy oxide nanomaterials. Background Technology

[0002] Multilayer ceramic chip capacitors (MLCCs) possess advantages such as high specific capacitance, high reliability, high withstand voltage, and excellent frequency characteristics, making them widely used in fields such as electronics, computers, automatic control, and communications. As electronic devices and components evolve towards miniaturization, thinning, and hybrid integration, MLCCs are moving towards miniaturization, larger capacitance, and thinner dielectric layers, which places higher demands on the performance and reliability of dielectric materials.

[0003] Barium titanate, as a core material of multilayer ceramic capacitors (MLCCs), has advantages such as low cost, no pollution and outstanding dielectric properties. However, it also has problems such as low breakdown strength, poor high-temperature stability and high residual polarization, resulting in low energy storage density and efficiency, which cannot meet the requirements of high-temperature applications and high energy storage density. Therefore, it is urgent to improve its energy storage performance.

[0004] High-entropy ceramics (HECs) have attracted much attention in materials research due to their excellent mechanical, physical, and chemical properties. They typically consist of a single-phase ionic crystal formed by at least five main cations or anions in equal or near-equal molar ratios. Lattice distortion in these crystals generates a slow diffusion effect, resulting in a fine-grained microstructure. According to relevant theories of dielectric ceramics, reducing grain size can significantly improve breakdown strength. Inspired by the high-entropy design concept, the fabrication of high-entropy dielectric ceramics based on BaTiO3 is of great significance for overcoming existing bottlenecks and improving the limited dielectric properties of materials.

[0005] To meet the development needs of MLCCs, developing high-entropy barium titanate-based perovskite materials with nanoscale high dielectric constants and wide temperature range stability has become a core research objective. Currently, methods for synthesizing high-entropy oxides (HEOs), such as sol-gel and solvothermal methods, are mostly complex. Controlling the phase and size of HEO particles requires long processing times, and the preparation process is cumbersome, making it difficult to meet the needs of large-scale production. Solid-state synthesis methods involve mixing raw materials such as metal oxides or metal salts in a certain proportion and carrying out a solid-state reaction at high temperature to prepare HEOs. This method is relatively simple to operate and does not require sophisticated equipment. For example, using conventional solid-state technology, stoichiometric Bi₂O₃, K₂CO₃, Na₂CO₃, La₂O₃, BaCO₃, and TiO₂ powders are wet-mixed in an ethanol solution, ball-milled at 400 rpm for 12 hours, calcined at 900℃ for 4 hours, and then cooled in a furnace to obtain (Bi₂O₃) particles with a size of approximately 550 nm. 0.2 Na 0.2 Ba 0.2 K 0.2 La0.2 TiO3 nanofiller. However, it is worth noting that high-temperature reactions can easily lead to grain growth and uneven element distribution, and the reaction time is long, energy consumption is high, and the purity and performance of the product are greatly affected by the uniformity of raw material mixing.

[0006] Furthermore, related technologies also employ thermal plasma technology to synthesize (Mn,Fe,Co,Ni,Cu)3O4 high-entropy oxide nanoparticles under conditions of 11kW input power and argon and carbon dioxide as plasma-generating gases. Experimental results show that the obtained nanoparticles are spherical or quasi-spherical with an average particle size of approximately 24 nm, but exhibit significant size inhomogeneity. Moreover, the preparation of single-phase high-entropy oxides using thermal plasma technology faces significant challenges: on the one hand, the extreme thermodynamic conditions and heterogeneous reaction environment of the high-temperature plasma region (>5000K) lead to differences in the volatilization rates of metal elements; on the other hand, significant component segregation occurs during rapid quenching, ultimately causing the product composition to deviate from the initial equimolar concentration, accompanied by the formation of metastable secondary phases and unexpected phases. Therefore, it is difficult to obtain high-entropy oxide materials with the required phase purity.

[0007] In summary, given the shortcomings of traditional preparation methods, such as insufficient component control and excessively large particle size, constructing a simple and effective synthetic method for barium titanate-based high-entropy oxides with precise component control and nanoscale small size has become a current research focus. Summary of the Invention

[0008] In view of this, the purpose of the present invention is to provide a method for preparing barium titanate-based high-entropy oxide nanomaterials, wherein the barium titanate-based high-entropy oxide nanomaterials prepared by the method are small in size and have high crystallinity.

[0009] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing barium titanate-based high-entropy oxide nanomaterials, comprising the following steps: The aqueous solutions of the metal salt and the precipitant were pumped separately into the mixer of the microchannel reactor for mixing and aging to obtain the barium titanate-based high-entropy precursor. The metal salts include divalent metal salts and tetravalent metal salts; the divalent metal salts include barium salts, or barium salts and auxiliary divalent metal salts; the tetravalent metal salts include titanium salts, or titanium salts and auxiliary tetravalent metal salts. The barium titanate-based high-entropy precursor, barium source, and water are mixed and subjected to a hydrothermal reaction to obtain barium titanate-based high-entropy oxide nanomaterials.

[0010] Preferably, the auxiliary divalent metal salt includes calcium salt and / or strontium salt; the auxiliary tetravalent metal salt includes one or more of tin salt, zirconium salt and hafnium salt.

[0011] Preferably, the molar ratio of the divalent metal salt to the tetravalent metal salt is (1~2):(1~2).

[0012] Preferably, the precipitant is sodium hydroxide.

[0013] Preferably, the molar ratio of the tetravalent metal salt to the precipitant is 1:(2~10).

[0014] Preferably, the flow rates of the aqueous solution of the metal salt and the aqueous solution of the precipitant are independently 20~60 mL / min.

[0015] Preferably, the temperature of the hydrothermal reaction is 120~220℃, and the holding time is 2~96h.

[0016] Preferably, the temperature of the mixing reaction is 80~100℃.

[0017] Preferably, the aging process is carried out under conditions of water bath and stirring; the temperature of the water bath is 80~100℃; and the stirring rate is 200~300rpm.

[0018] Preferably, the barium source is barium hydroxide; the molar ratio of the barium source to the barium titanate-based high-entropy precursor is (1~2):1.

[0019] This invention provides a method for preparing barium titanate-based high-entropy oxide nanomaterials, comprising the following steps: pumping an aqueous solution of a metal salt and an aqueous solution of a precipitant into a mixer of a microchannel reactor for mixing and aging to obtain a barium titanate-based high-entropy precursor; wherein the metal salt includes divalent and tetravalent metal salts; wherein the divalent metal salt includes barium salt, or barium salt and auxiliary divalent metal salt; wherein the tetravalent metal salt includes titanium salt, or titanium salt and auxiliary tetravalent metal salt; and mixing the barium titanate-based high-entropy precursor, a barium source, and water for a hydrothermal reaction to obtain barium titanate-based high-entropy oxide nanomaterials.

[0020] This invention first utilizes a microchannel reactor to prepare barium titanate-based high-entropy precursors via co-precipitation. Differences in solubility products between different systems pose challenges to the precise and controllable preparation of multi-component materials. Compared to traditional reactors, microchannel reactors significantly improve heat transfer efficiency, mass transfer efficiency, and micro-mixing effects during the reaction process. They also offer strong control over reaction temperature and concentration distribution, facilitating the formation of a uniform reaction environment and overcoming solubility product differences between different systems. This provides a precise and controllable pathway for the preparation of multi-component precursors. Subsequently, an auxiliary hydrothermal reaction promotes crystallization, resulting in small-sized, highly crystalline nanoscale barium titanate-based high-entropy oxide materials.

[0021] The preparation method provided by this invention can efficiently and stably prepare small-sized, highly crystalline barium titanate-based high-entropy oxide nanoparticles, overcoming the shortcomings of traditional processes and making it suitable for large-scale industrial production. Attached Figure Description

[0022] Figure 1 Ba(Ti) prepared in Example 1 1 / 3 Zr 1 / 3 Sn 1 / 3 XRD pattern of O3 powder; Figure 2 Ba(Ti) prepared in Example 1 1 / 3 Zr 1 / 3 Sn 1 / 3 TEM image of O3 powder; Figure 3 Ba(Ti) prepared in Example 2 1 / 3 Zr 1 / 3 Hf 1 / 3 XRD pattern of O3 powder; Figure 4 Ba(Ti) prepared in Example 2 1 / 3 Zr 1 / 3 Hf 1 / 3 TEM image of O3 powder; Figure 5 Ba(Ti) prepared in Example 3 1 / 3 Sn 1 / 3 Hf 1 / 3 XRD pattern of O3 powder; Figure 6 Ba(Ti) prepared in Example 3 1 / 3 Sn 1 / 3 Hf 1 / 3 TEM image of O3 powder; Figure 7 Ba(Ti) prepared in Example 4 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 XRD pattern of O3 powder; Figure 8 Ba(Ti) prepared in Example 4 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 TEM image of O3 powder; Figure 9 (Ba) prepared in Example 5 1 / 3 Sr 1 / 3 Ca 1 / 3 XRD pattern of TiO3 powder; Figure 10 (Ba) prepared in Example 51 / 3 Sr 1 / 3 Ca 1 / 3 TEM image of TiO3 powder; Figure 11 (Ba) prepared in Example 6 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 XRD pattern of O3 powder; Figure 12 (Ba) prepared in Example 6 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 TEM image of O3 powder; Figure 13 (Ba) prepared in Example 7 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 XRD pattern of O3 powder; Figure 14 (Ba) prepared in Example 7 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 TEM image of O3 powder; Figure 15 (Ba) prepared in Example 8 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 XRD pattern of O3 powder; Figure 16 (Ba) prepared in Example 8 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 TEM image of O3 powder; Figure 17 (Ba) prepared in Example 9 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 4 Zr 1 / 4 Sn1 / 4 Hf 1 / 4 XRD pattern of O3 powder; Figure 18 (Ba) prepared in Example 9 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 TEM image of O3 powder; Figures 19-21 The samples prepared by the conventional solid-state method in Comparative Example 1 are (Ba) 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3Hf 1 / 3 O3(a), (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 O3(b), (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 Size distribution diagram of O3(c) powder. Detailed Implementation

[0023] This invention provides a method for preparing barium titanate-based high-entropy oxide nanomaterials, comprising the following steps: The aqueous solutions of the metal salt and the precipitant were pumped separately into the mixer of the microchannel reactor for mixing and aging to obtain the barium titanate-based high-entropy precursor. The metal salts include divalent metal salts and tetravalent metal salts; the divalent metal salts include barium salts, or barium salts and auxiliary divalent metal salts; the tetravalent metal salts include titanium salts, or titanium salts and auxiliary tetravalent metal salts. The barium titanate-based high-entropy precursor, barium source, and water are mixed and subjected to a hydrothermal reaction to obtain barium titanate-based high-entropy oxide nanomaterials.

[0024] Unless otherwise specified, the present invention does not have special requirements on the source of raw materials used, and commercially available products well known to those skilled in the art can be used.

[0025] In this invention, an aqueous solution of a metal salt and an aqueous solution of a precipitant are pumped separately into a mixer of a microchannel reactor for mixing and aging to obtain a barium titanate-based high-entropy precursor.

[0026] In one embodiment, the metal salt includes divalent and tetravalent metal salts; the divalent metal salt includes barium salt, or barium salt and auxiliary divalent metal salt; the tetravalent metal salt includes titanium salt, or titanium salt and auxiliary tetravalent metal salt; the auxiliary divalent metal salt includes one or more of calcium salt and strontium salt; the auxiliary tetravalent metal salt includes one or more of tin salt, zirconium salt and hafnium salt, specifically tin salt, zirconium salt or hafnium salt in a specific embodiment; the barium salt is barium dichloride; the calcium salt is calcium dichloride; the strontium salt is strontium dichloride; the titanium salt is titanium tetrachloride; the tin salt is tin tetrachloride; the zirconium salt is zirconium oxychloride; the hafnium salt is hafnium tetrachloride; the precipitant is sodium hydroxide; and the aqueous solution of the metal salt contains gold... The concentration of the metal salt is 0.2~0.3 mol / L, specifically 0.25 mol / L in this embodiment; the concentration of the precipitant in the aqueous solution is 0.5~2.5 mol / L, specifically 2.5 mol / L in this embodiment; the molar ratio of the tetravalent metal salt to the precipitant is 1:(2~10), specifically 1:10 in this embodiment; the molar ratio of the divalent metal salt to the tetravalent metal salt is (1~2):(1~2), specifically 1:1 or 1.5:1 in this embodiment; when the divalent metal salt is a mixture of several divalent metal salts, the amount of each divalent metal salt is equal; when the tetravalent metal salt is a mixture of several tetravalent metal salts, the amount of each tetravalent metal salt is equal.

[0027] In one embodiment, the flow rates of the aqueous solutions of the metal salt and the precipitant are independently 20-60 mL / min, specifically 50 mL / min in this embodiment; the temperature of the mixing reaction is 80-100°C, specifically 80°C in this embodiment; and the reaction time is 5-10 min, specifically 8 min in this embodiment. Increasing the flow rate decreases the precursor size; increasing the proportion and concentration of the precipitant, or increasing the reaction temperature, increases the precursor size. The precursor exists in precipitated form.

[0028] In one embodiment, the aging process is carried out under water bath and stirring conditions; the temperature of the water bath is 80~100℃, specifically 80℃ in this embodiment; the stirring speed is 200~300rpm, specifically 280rpm in this embodiment; and the aging time is 60~80min, specifically 60min in this embodiment.

[0029] As one implementation method, the aging process further includes: removing the supernatant from the aged slurry through sedimentation, followed by washing and filtration to obtain the barium titanate-based high-entropy precursor.

[0030] In one embodiment, the precipitation is carried out by centrifugation or static precipitation; the centrifugation speed is 8000~10000 rpm, the time is 3~5 min, and the temperature is 25~30℃; the static precipitation time is 6~12 h, and in a specific embodiment it is 12 h; the washing reagent is glacial acetic acid solution; the concentration of the glacial acetic acid solution is 0.1~1 mol / L, and in a specific embodiment it is 0.5 mol / L.

[0031] In one embodiment, the size of the barium titanate-based high-entropy precursor is 20~200nm, and in a specific embodiment it is 50~100nm.

[0032] This invention utilizes a microchannel reactor to precisely control the formation of barium titanate-based high-entropy oxide precursors under confined reaction conditions, obtaining small-sized and highly active precursors. These precursors are then combined with a hydrothermal reaction to prepare small-sized barium titanate-based high-entropy oxide nanoparticles. The high-frequency collisions of small molecules in the A source (an aqueous solution of the metal salt) and B source (an aqueous solution of the precipitant) of the barium titanate-based high-entropy oxide precursor within the microchannel mixer rapidly complete the nucleation process, forming highly active small-sized precursors. This provides high-quality raw materials for the subsequent hydrothermal reaction, promoting the formation of small-sized barium titanate-based high-entropy oxides. Compared to traditional solid-state and hydrothermal methods, this invention avoids high-temperature calcination and the use of complex equipment. By combining microchannels and hydrothermal methods, it achieves stable generation of barium titanate-based high-entropy oxides under mild conditions, resulting in a simple process suitable for industrial production. This invention effectively overcomes the problems of large particle size and poor phase structure stability in traditional preparation techniques by optimizing the mixing conditions of the microchannel reactor, and produces nanoscale barium titanate-based high-entropy oxides, thus expanding the application of perovskite materials in high-end electronic components.

[0033] The physical confinement effect of microchannel reactors can constrain the grain growth direction and form smaller grains. Small grains have higher surface energy, but the uniform nucleation of microchannels can offset grain boundary stress and avoid phase separation caused by wide grain size distribution in traditional methods. This allows for the preparation of barium titanate-based high-entropy oxide nanomaterials with small size and stable phase structure.

[0034] After obtaining the barium titanate-based high-entropy precursor, the present invention mixes the barium titanate-based high-entropy precursor, a barium source, and water, and carries out a hydrothermal reaction to obtain barium titanate-based high-entropy oxide nanomaterials.

[0035] In one embodiment, the barium source is one or more of barium hydroxide, barium chloride, barium sulfate, and barium carbonate, with barium hydroxide being used in a specific embodiment; the molar ratio of the barium source to the barium titanate-based high-entropy precursor is (1~2):1, with 1.5:1 being used in a specific embodiment; the water is deionized water; the volume of the mixture of the barium titanate-based high-entropy precursor, the barium source, and the water is 60~80% of the volume of the reaction vessel used for the hydrothermal reaction, with 70% being used in a specific embodiment; the reaction vessel is a reaction kettle.

[0036] In one embodiment, the temperature of the hydrothermal reaction is 120~220℃, specifically 220℃, and the holding time is 2~96h, specifically 24h.

[0037] During the hydrothermal reaction, Ba 2+ With Ti 4+ BaTiO3 is generated under alkaline conditions, with Ba at the A-site and Ti at the B-site. Based on this, the A-site element is extended to Ba / Ca / Sr, and the B-site element is extended to Ti / Sn / Hf / Zr, with the molar ratio of each element at each site being the same, to generate ABO3 (Ba / Ca / Sr at the A-site and Ti / Sn / Hf / Zr at the B-site). Increasing the hydrothermal reaction temperature increases the crystallinity and size of the powder, but has no effect on the morphology; increasing the hydrothermal time also increases the crystallinity and size of the powder, but has no effect on the morphology.

[0038] As one embodiment, after the hydrothermal reaction, the process further includes: sequentially cooling, separating solids and liquids, washing, drying and grinding the product obtained from the hydrothermal reaction to obtain barium titanate-based high-entropy oxide nanoparticle powder.

[0039] In one implementation method, the solid-liquid separation is centrifugation; the centrifugation speed is 8000~10000 rpm, specifically 8000~9000 rpm, the time is 3~5 min, specifically 3~4 min, and the temperature is 25~30℃, specifically 25℃; the washing reagents are acetic acid solution and deionized water; the concentration of the acetic acid solution is 0.05~0.10 mol / L; the number of washes with acetic acid solution and deionized water is 3~5 times, specifically 3 times; the drying temperature is 80~100℃, specifically 80℃, and the time is 12~36 h, specifically 36 h; the grinding is manual grinding.

[0040] In one embodiment, the size of the barium titanate-based high-entropy oxide nanomaterial is 50~150nm, and in specific embodiments it is 65.9nm, 66.0nm, 69.6nm, 70.3nm, 70.7nm, 71.5nm, 72.1nm, 75.8nm or 97.8nm.

[0041] This invention utilizes the highly efficient mass transfer properties of microchannel reactors, enabling rapid and uniform mixing of reactants within a short time. Through high-frequency collisions at the molecular level, a high-entropy precursor with controllable composition is prepared. Furthermore, a mild hydrothermal reaction promotes the formation of nanoscale barium titanate-based high-entropy oxides.

[0042] Compared to traditional preparation methods, which suffer from insufficient component control and excessively large particle sizes, the method provided by this invention can generate barium titanate-based high-entropy nano-oxide materials with high crystallinity and small particle size under relatively mild conditions. Furthermore, this method exhibits good reproducibility and potential for industrial production.

[0043] Compared with these traditional methods, the present invention has the following significant advantages: 1. Advantages in particle size control: Compared with the traditional solid-phase method, the microchannel reactor can prepare high-entropy precursors with small particle size and high reactivity by precisely controlling the reaction conditions. This provides ideal raw materials for subsequent hydrothermal reactions, ultimately yielding nanoscale barium titanate-based high-entropy oxide particles. In contrast, high-entropy barium titanate prepared by the solid-phase method usually has a larger particle size and uneven particle size distribution.

[0044] 2. Improved Overall Performance of Barium Titanate: Compared to traditional barium titanate, barium titanate-based high-entropy oxides exhibit a significant improvement in dielectric constant. By introducing the concept of high entropy, barium titanate materials achieve a wider temperature range and lower dielectric loss. Through design paradigms that emphasize complex composition, nanostructure, and intelligent functionality, the performance limitations of traditional barium titanate have been overcome, demonstrating significant application potential in multiple cutting-edge fields.

[0045] The concept of high entropy originates from high entropy alloys, referring to the formation of a stable phase with high configurational entropy by introducing highly disordered solid solutions of multiple elements at specific sites in the crystal structure. In high-entropy perovskites, the synergistic effect of multiple elements can hinder phase separation caused by lattice thermal vibrations. The increase in entropy offsets the adverse effects of enthalpy change, allowing the material to remain a single phase over a wide temperature range. This avoids the multiphase coexistence problem caused by temperature changes in traditional perovskites, thereby reducing dielectric loss.

[0046] 3. Suitable for industrial production: The precise flow rate control and rapid mixing characteristics of microchannel reactors greatly improve the controllability of the reaction, make process parameters easier to adjust and optimize, and have better repeatability, shorter reaction time, and higher process stability, making them suitable for large-scale industrial production.

[0047] In summary, this invention uses a microchannel reactor combined with a hydrothermal method to obtain small-sized nanoscale barium titanate-based high-entropy oxide materials simply and effectively. Furthermore, the introduction of the high-entropy concept enhances or broadens the overall dielectric properties of barium titanate-based ceramic materials, demonstrating significant industrial application value.

[0048] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention, but they should not be construed as limiting the scope of protection of the present invention.

[0049] Example 1 (1) Reaction procedure: Prepare 0.25 mol / L solution containing an equimolar amount of Ti 4+ Zr 4+ and Sn 4+ An aqueous solution of 0.375 mol / L BaCl2 and a 0.375 mol / L BaCl2 solution were used as the aqueous solution of the metal salt, and an aqueous solution of 2.5 mol / L sodium hydroxide was used as the aqueous solution of the precipitant. Both solutions were heated to 80 °C in a water bath and then mixed in a microchannel reactor at flow rates of 50 mL / min and 50 mL / min respectively. The molar ratio of sodium hydroxide to the metal element in the tetravalent metal salt was 10:1. The flow rate of the solution in the microchannel reactor was controlled by a delivery pump, and rapid mixing was achieved to realize molecular collision nucleation reaction, yielding Ba(Ti)2. 1 / 3 Zr 1 / 3 Sn 1 / 3 O3 precursor slurry; (2) Slurry aging: The Ba(Ti) obtained in step (1) is aged. 1 / 3 Zr 1 / 3 Sn 1 / 3 O3 precursor (particle size 57nm) slurry was placed in a three-necked flask and aged for 60 min under conditions of 80℃ water bath and 280rpm stirring. (3) Precipitation separation and washing: After aging, the aged Ba(Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 The O3 precursor slurry was allowed to stand for 12 hours to remove the supernatant. Then, the slurry was washed with 0.5 mol / L glacial acetic acid solution to ensure that impurities were completely removed. (4) Hydrothermal reaction: After washing, the slurry was filtered to obtain a thick precursor reactant. After determining the solid content, the precursor reactant was placed in a 25 mL polytetrafluoroethylene-lined reactor. Barium hydroxide octahydrate was added according to the molar ratio of barium source to precursor reactant of 1.5:1, and deionized water was added until the filling degree was 70%. The reactor was placed in an oven at 220℃ for hydrothermal reaction for 24 h. (5) Product processing: After the hydrothermal reaction was completed, the product was cooled to room temperature of 25°C and centrifuged at 8000 rpm for 3 min. The resulting solid was washed three times each with 0.5 mol / L glacial acetic acid and deionized water, and then dried in an oven at 80°C for 36 h. The dried product was then manually ground to obtain Ba(Ti 1 / 3 Zr 1 / 3 Sn 1 / 3 )O3 powder.

[0050] Example 2 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ti. 4+ Zr 4+ and Hf 4+ The chloride salt was mixed and reacted in a microchannel reactor to obtain the product Ba(Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 )O3.

[0051] Example 3 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ti. 4+ Sn 4+ and Hf 4+ The chloride salt was mixed and reacted in a microchannel reactor to obtain the product Ba(Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 )O3.

[0052] Example 4 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ti. 4+ Zr 4+ Sn 4+ and Hf 4+ The chloride salt was mixed and reacted in a microchannel reactor to obtain the product Ba(Ti) 1 / 4 Zr 1 / 4Sn 1 / 4 Hf 1 / 4 )O3.

[0053] Example 5 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with Ti. 4+ The chloride salt and divalent metal salt are replaced with an equal amount of Ba. 2+ 、Sr 2+ and Ca 2+ The chloride salt was mixed and reacted in a microchannel reactor to obtain the product (Ba). 1 / 3 Sr1 / 3 Ca 1 / 3 TiO3.

[0054] Example 6 The difference from Example 1 is that the divalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ba. 2+ 、Sr 2+ and Ca 2+ The chloride salt was mixed and reacted in a microchannel reactor to obtain the product (Ba). 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 )O3.

[0055] Example 7 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ti. 4+ Zr 4+ and Hf 4+ The chloride salt and divalent metal salt are replaced with an equal amount of Ba. 2+ 、Sr 2+ and Ca 2+ The chloride salt was mixed and reacted in a microchannel reactor to obtain the product (Ba). 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 )O3.

[0056] Example 8 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ti. 4+ Sn 4+ and Hf 4+ The chloride salt and divalent metal salt are replaced with an equal amount of Ba. 2+ 、Sr 2+ and Ca 2+ The chloride salt yields a product (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 )O3.

[0057] Example 9 The difference from Example 1 is that the tetravalent metal salt in the aqueous solution of the metal salt is replaced with an equal amount of Ti. 4+ Zr 4+ Sn4+ and Hf 4+ The chloride salt and divalent metal salt are replaced with an equal amount of Ba. 2+ 、Sr 2+ and Ca 2+ The chloride salt yields a product (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 )O3.

[0058] Comparative Example 1 The difference from Example 1 is that the products in Examples 6, 7, and 8 were synthesized using a conventional solid-state synthesis method with CaCO3, SrCO3, BaCO3, TiO2, SnO2, ZrO2, and HfO2 as raw materials, followed by wet ball milling and calcination at 900°C for 5 hours in a muffle furnace. The average particle sizes obtained were 564 nm, 160 nm, and 727 nm, respectively. This demonstrates that, while synthesizing the same product, the method mentioned in this invention can synthesize products with smaller particle sizes.

[0059] Performance testing Figure 1 Ba(Ti) prepared in Example 1 1 / 3 Zr 1 / 3 Sn 1 / 3 XRD pattern of O3 powder. Figure 2 Ba(Ti) prepared in Example 1 1 / 3 Zr 1 / 3 Sn 1 / 3 TEM image of O3 powder, such as Figure 1 , Figure 2 As shown, Ba(Ti 1 / 3 Zr 1 / 3 Sn 1 / 3 The average particle size of the O3 powder is 69.6 nm, which indicates that the crystal development is relatively complete, there are no voids or defects inside, and the elements are evenly distributed inside.

[0060] Figure 3 Ba(Ti) prepared in Example 2 1 / 3 Zr 1 / 3 Hf 1 / 3 XRD pattern of O3 powder. Figure 4 Ba(Ti) prepared in Example 2 1 / 3 Zr 1 / 3 Hf 1 / 3 TEM image of O3 powder, such as Figure 3 , Figure 4 As shown, Ba(Ti 1 / 3 Zr1 / 3 Hf 1 / 3 The average particle size of the O3 powder is 71.5 nm.

[0061] Figure 5 Ba(Ti) prepared in Example 3 1 / 3 Sn 1 / 3 Hf 1 / 3 XRD pattern of O3 powder. Figure 6 Ba(Ti) prepared in Example 3 1 / 3 Sn 1 / 3 Hf 1 / 3 TEM image of O3 powder, such as Figure 5 , Figure 6 As shown, Ba(Ti 1 / 3 Sn 1 / 3 Hf 1 / 3 The average particle size of the O3 powder is 97.8 nm.

[0062] Figure 7 Ba(Ti) prepared in Example 4 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 XRD pattern of O3 powder. Figure 8 Ba(Ti) prepared in Example 4 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 TEM image of O3 powder, such as Figure 7 , Figure 8 As shown, Ba(Ti 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 The average particle size of the O3 powder is 70.7 nm.

[0063] Figure 9 (Ba) prepared in Example 5 1 / 3 Sr 1 / 3 Ca 1 / 3 XRD pattern of TiO3 powder. Figure 10 (Ba) prepared in Example 5 1 / 3 Sr 1 / 3 Ca 1 / 3 TEM image of TiO3 powder, as shown Figure 9 , Figure 10 As shown, (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 The average particle size of TiO3 powder is 70.3 nm.

[0064] Figure 11 (Ba) prepared in Example 61 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 XRD pattern of O3 powder. Figure 12 (Ba) prepared in Example 6 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 TEM image of O3 powder, such as Figure 11 , Figure 12 As shown, (Ba 1 / 3Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 The average particle size of the O3 powder is 66.0 nm.

[0065] Figure 13 (Ba) prepared in Example 7 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 XRD pattern of O3 powder. Figure 14 (Ba) prepared in Example 7 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 TEM image of O3 powder, such as Figure 13 , Figure 14 As shown, (Ba 1 / 3Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Hf 1 / 3 The average particle size of the O3 powder is 72.1 nm.

[0066] Figure 15 (Ba) prepared in Example 8 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 XRD pattern of O3 powder. Figure 16 (Ba) prepared in Example 8 1 / 3 Sr 1 / 3 Ca1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 TEM image of O3 powder, such as Figure 15 , Figure 16 As shown, (Ba 1 / 3Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Sn 1 / 3 Hf 1 / 3 The average particle size of the O3 powder is 75.8 nm.

[0067] Figure 17 (Ba) prepared in Example 9 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 XRD pattern of O3 powder. Figure 18 (Ba) prepared in Example 9 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 TEM image of O3 powder, such as Figure 17 , Figure 18 As shown, (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 4 Zr 1 / 4 Sn 1 / 4 Hf 1 / 4 The average particle size of the O3 powder is 65.9 nm.

[0068] Figures 19-21 The samples prepared by the conventional solid-state method in Comparative Example 1 are (Ba) 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3Hf 1 / 3 O3(a), (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3 Zr 1 / 3 Sn 1 / 3 O3(b), (Ba 1 / 3 Sr 1 / 3 Ca 1 / 3 (Ti) 1 / 3Sn 1 / 3 Hf 1 / 3 Size distribution diagram of O3(c) powder. From Figures 19-21 It can be seen that, when synthesizing the same product, the method mentioned in this invention can synthesize a product with a smaller size.

[0069] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing barium titanate-based high-entropy oxide nanomaterials, characterized in that, Includes the following steps: The aqueous solutions of the metal salt and the precipitant were pumped separately into the mixer of the microchannel reactor for mixing and aging to obtain the barium titanate-based high-entropy precursor. The metal salts include divalent metal salts and tetravalent metal salts; the divalent metal salts include barium salts, or barium salts and auxiliary divalent metal salts; the tetravalent metal salts include titanium salts, or titanium salts and auxiliary tetravalent metal salts. The barium titanate-based high-entropy precursor, barium source, and water are mixed and subjected to a hydrothermal reaction to obtain barium titanate-based high-entropy oxide nanomaterials.

2. The preparation method according to claim 1, characterized in that, The auxiliary divalent metal salt includes calcium salt and / or strontium salt; the auxiliary tetravalent metal salt includes one or more of tin salt, zirconium salt and hafnium salt.

3. The preparation method according to claim 1 or 2, characterized in that, The molar ratio of the divalent metal salt to the tetravalent metal salt is (1~2):(1~2).

4. The preparation method according to claim 1, characterized in that, The precipitant is sodium hydroxide.

5. The preparation method according to claim 1 or 4, characterized in that, The molar ratio of the tetravalent metal salt to the precipitant is 1:(2~10).

6. The preparation method according to claim 1, characterized in that, The flow rates of the aqueous solutions of the metal salt and the precipitant are independently 20-60 mL / min.

7. The preparation method according to claim 1, characterized in that, The hydrothermal reaction temperature is 120~220℃, and the holding time is 2~96h.

8. The preparation method according to claim 1, characterized in that, The temperature of the mixing reaction is 80~100℃.

9. The preparation method according to claim 1, characterized in that, The aging process is carried out under conditions of water bath and stirring; the temperature of the water bath is 80~100℃; and the stirring speed is 200~300rpm.

10. The preparation method according to claim 1, characterized in that, The barium source is barium hydroxide; the molar ratio of the barium source to the barium titanate-based high-entropy precursor is (1~2):1.